Development of Doctrine of Frustration: Departure from Absolutism in Contracts - Nawaz, Hafiz Muhammad Usman; Baig, Mirza Shahid Rizwan; Idrees, Dr. Rao Qasim (Journal of Peace, Development and Communication, 2021)
Absolute liability in contracts or absolutism is traced back to seventeenth century. The famous case of Paradine v Jane (1647) laid down the basic rule of absolute liability in contracts. The rule stated that contracting parties are bound to fulfill their promises irrespective of circumstances. This case is considered as an authority in absolute liability in contracts. In order to excuse the party not performing his contractual obligations due to no fault on his part, doctrine of frustration of contract was developed. Taylor v Caldwell (1863) is generally considered a turning point in the application of absolute liability in contracts. It provided a new avenue for discharge of contracts on the ground of supervening impossibility. This article deals with the factors responsible for the development of doctrine of frustration of contract. Especially case laws will be discussed which had changed the doctrine of absolute liability in the performance of contracts and this new doctrine has been emerged.